[Rezension von: M. Spataro, M. Furholt (eds), Detecting and explaining technological innovation in prehistory] - Wilde, Heike (Archäologische Informationen, 2021)
Rezension zu: Spataro, M. & Furholt, M. (eds) (2020). Detecting and explaining technological innovation in prehistory. (Scales of Transformation in Prehistoric and Archaic Societies, 8). Leiden: Sidestone Press. 248 Seiten, 22 S/W u. 37 farbige Abb. ISBN-13: 9789088908255 Open Access: https://www.sidestone.com/books/detectingand-explaining-technological-innovation-inprehistory